Impact of ABC pathway adherence in high-risk patients with atrial fibrillation: an analysis from the ESC-EHRA EORP-AF long-term general registry. (3rd October 2022) - Ding, W Y; Proietti, M; Romiti, G F; Vitolo, M; Fawzy, A M; Boriani, G; Marin, F; Blomstrom-Lundqvist, C; Potpara, T S; Fauchier, L; Lip, G Y H
Abstract: Background: The impact of Atrial Fibrillation Better Care (ABC) pathway adherence among high-risk subgroups of patients with atrial fibrillation (AF), ie. those with chronic kidney disease (CKD), advanced age and/or prior thromboembolism remains unknown. We evaluated the impact of ABC pathway adherence on clinical outcomes in these high-risk AF patients. Methods: The EORP-AF General Long-Term Registry is a prospective, observational registry from 250 centres across 27 European countries. High-risk patients were defined as those with either CKD (eGFR <60 mL/min/1.73 m 2 ), older age (≥75 years) and/or prior thromboembolism. The primary outcome was a composite event of all-cause death, any thromboembolism and acute coronary syndrome, evaluated according to ABC pathway adherence. Results: A total of 6646 patients with AF were included (median age was 70 [IQR 61–77] years; 40.2% females). There were 3304 (54.2%) `high risk' patients with either CKD (n=1750), older age (n=2236) or prior thromboembolism (n=728). Among these there were 924 (28.0%) managed as adherent to ABC. At 2-year follow-up, a total of 966 (14.5%) patients reported the primary outcome. The incidence of the primary outcome was significantly lower in high-risk patients managed as adherent to ABC pathway (IRR 0.53 [95% CI, 0.43–0.64]). Consistent results were obtained in the individual subgroups [Table]. Using multivariable Cox proportional hazards analysis, ABC adherence in the high-risk cohort was independently associated with a lower risk of primary outcome (aHR 0.64 [95% CI, 0.51–0.80]), as well as in the CKD (aHR 0.51 [95% CI, 0.37–0.70]) and elderly subgroups (aHR 0.69 [95% CI, 0.53–0.90]). Overall, there was greater reduction in the risk of primary outcome as more ABC criteria were fulfilled, both in the overall high-risk patients, as well as in the individual subgroups [Figure]. Conclusion: In a large, contemporary European AF cohort there was a significant proportion of high-risk patients. Among these, a low prevalence of integrated care, as assessed by adherence to ABC pathway, was found. Nonetheless, a clinical management adherent to the ABC pathway was associated with a significant reduction in the risk of adverse outcomes, the benefits of which were more significant with increasing number of ABC criteria adherent. Funding Acknowledgement: Type of funding sources: None.